Faize alternatif bir finansman aracı olarak Karz-ı Hasen yerine zekât - KAAN, ENVER OSMAN (My University, 2021)
Zekât, İslam ibadet esaslarından biri olarak farz kılınmıştır. Faiz ise Allah’a ve resulüne harp ilan etmek kadar ağır bir işlem görülerek haram kılınmıştır. Kur’an’ı Kerim’de faiz ile zekât karşılaştırılarak; verilen faizin Allah katında artmayacağı, buna karşın Allah’ın rızası gözetilerek verilen zekâtın kat kat artacağı beyan edilmiştir. Hâlbuki faiz bir borç işlemidir, borç işleminde verilenin geri alınması söz konusudur. Zekât ise geri alınmamak üzere verilen maldır. Kur’an’ı Kerim’de borç vermekle ilgili kullanılan karz-ı hasen kavramı “güzel borç” anlamına gelir. Dolayısıyla, karz-ı hasen de bir borç işlemi olduğuna göre bu kavramın faiz ile karşılaştırmalı olarak ele alınmaması dikkat çekmektedir. Zekât ile faiz ekonomik, siyasi, sosyal ve ahlaki boyutları olan iki önemli kavramdır. Bu iki kavramı sadece ekonomi penceresinden değerlendirmek orantısız bilgi karşılaştırmasına neden olmakta ve faizin karz-ı hasen yerine zekât ile mukayesesinin anlaşılması zorlaşmaktadır. İşte makalede faiz ile karz-ı hasen kavramının neden karşılaştırmalı ele alınmadığının izahı yapılmaya çalışılacaktır. Ayrıca faiz, verilen borcun fazlasıyla geri alınması yani verilen paranın artması demektir. Zekât ise, malın bir kısmını geri almamak üzere başkasına vermek yani maldan eksilt me yapmaktır. Görünüşte asıl artma faizde yaşandığı halde, ayette artış vurgusunun zekâtta yapılmasının piyasaya yansıması üzerinde durulacaktır.

Zakāt has been made obligatory as one of the principles of Islamic worship. Interest, on the other hand, was rendered unlawful by being treated as harshly as declaring war against Allah and His Messenger. By comparing interest and zakāt in the Qur’ān; It has been declared that the interest given will not increase in the sight of Allah, whereas the zakāt given by observing Allah’s consent will increase many times over. However, interest is a debit transaction, it is possible to get back what is given in the debit transaction. Zakāt is the property that is given to not be taken back. The concept of qarẓ-ı hasan, which is used for lending in the Qur’ān, means “beautiful loan”. Certainly, zakāt and interest are two important concepts that have economic, political, social and moral dimensions. Evaluating these two concepts only from the perspective of economics causes information asymmetry and it is really difficult to understand the comparison of interest with zakāt instead of qarẓ-ı hasan. Therefore, since qarẓ-ı hasan is a debit transaction, it would be expected to consider this concept in comparison with interest. However, this was not done. One of the purposes of this article will be to explain why the concept of interest and qarẓ-ı hasan is not discussed comparatively. In addition, ribā (interest) means that the debit that is given interest is paid back, that is, the money given increases. Zakāt, on the other hand, is to give a part of the property to someone else without getting it back, that is, to make a decrease in the property. Although the real increase seemingly is a result of the interest transaction, the reflection of the real increase in zakāt in the verse will be emphasized in the commercial life, market conditions and economic system.
Zakāt instead of Qarz-ı Hasan as alternative finance tool to interest
Keywords: İslam Hukuku; Karz-ı Hasen; Zekât; Faiz; Finansman; Islamic Law; al-Qarẓ al-Hasan; Zakāt; Interest; Financing